Juridical Analysis of Gambling Offenders According to the Criminal Code - Muhlizar; Nelvitia Purba; Joharsah; Syafil Warman; M. Yusuf Iskandar (International Journal of Educational Research Excellence (IJERE), 2023)
Objective study This is to find out what is causing perpetrators to commit criminal gambling in Indonesia at the moment. According to the Criminal Code, how do you apply the law to your criminal gambling? What inhibitor in the application of criminal perpetrator criminal gambling complied with the Criminal Code? In accordance with the title and problem to be addressed discussed in the study, this can give useful results, so study This is done with the study of juridical normative (method study of law normative). Research methods: juridical normative is the study of law literature carried out with the method of researching ingredients in literature or secondary data. Factors that become reasons follow criminal gambling, namely: factors social and economic, situational, learning, perceptions about probability of victory, and perceptions of skills. Based on cases of gambling that occur in the jurisdiction of Southeast Aceh Police in general, it is a factor in social and economic society, where a low economy has stimulated perpetrators to engage in gambling. For increased economy as interpreters write (collectors) or as players (bettors) expect victory. Application law criminal perpetrator criminal gambling at the Southeast Aceh Police has been in accordance with provisions of the Criminal Procedure Code. Factors that become inhibitors in handling lawful criminals and perpetrators of criminal gambling at the Southeast Aceh Police are: related substances that follow criminal gambling There is an exclusion to activities given gambling permission so that activity is gambling. That includes following criminal gambling. Amount limited personnel and HR capabilities in identification elements gambling online (internet gambling). Found evidence from proof electronics that haven't been arranged in law, so it must be supported with information from an expert.